Space psychology: a comprehensive approach to the future of astronaut wellbeing - Nezami, Annahita (Frontiers in Virtual Reality, 2025)
As humanity embarks on Space Age II, the revival of human space exploration brings unprecedented opportunities and challenges. The commercial spaceflight industry has significantly lowered barriers, enabling government agencies to pursue more ambitious missions to the Moon and Mars in the coming decades. This renewed momentum necessitates a more comprehensive approach to the psychological and well-being aspects of human space exploration.Drawing on the authors training as a psychologist and co-founder of digital technology startup, this paper explores how immersive technologies, particularly Virtual Reality (VR) and advanced interfaces can address some of the unique psychological and social challenges posed by isolated, confined, and extreme (ICE) environments. It highlights the importance of integrating scientific and psychological theories into digital therapies to create comprehensive evidence-based interventions. These interventions aim to significantly improve the quality of life and mission success for future space explorers, offering more than stand-alone one-off solutions. This will require continuous innovation and research in leveraging advanced technologies to meet the evolving demands of human space exploration and habitation.